Evaluasi Radiografik Terhadap Ketinggian dan Densitas Tulang Alveolar Mandibula Setelah Penggunaan Gigi Tiruan Lengkap dengan Tissue Conditioner pada Wanita Pasca Menopause - Rahardyan Parnaadji; Zahreni Hamzah; Ady Soesetijo (Faculty of Dentistry, Universitas Indonesia, 2015)
The need for women to use a dental prosthesis increases with age. Low estrogen level is characteristic in post menopausal women. In this case, it often related with reduction of density and mandibular alveolar bone height. This study aimed to investigate the differences in density and mandibular alveolar bone height in post-manopausal women wearing complete dentures with tissue conditioner. The clinical observations were conducted on seven persons who had received a new set of complete denture in the Prosthodontic Department of the Dental Hospital of the Dental Faculty in Jember University. Balanced occlusion was used in all dentures, fabricated according to the principles used in the department. Panoramic radiographs had been made for all subjects as the baseline, and two, four, and six months later using dentures with tissue conditione. The data was analyzed by using one-way analysis of variance at the 0.05 level. The conclusion was that there is no significant difference in density and mandibular alveolar bone height of complete denture wearers with tissue conditioner in post-menopausal women.